Assessment of the Carbon Stock of Trees in Selected Urban Green Spaces of Davao City, Philippines - Daiseree Cuabo; Yves P.M. Montero; Daryl S. Salas; John P.M. Viernes (Applied Environmental Research, 2025)
The combined impacts of deforestation, tree cover loss, and urbanization in urban and suburban areas significantly reduce the capacity of natural carbon sinks to sequester and store carbon. Hence, this study assessed the aboveground biomass (AGB) and carbon stock of trees in the selected green spaces of Davao City. A purposive sampling technique was employed in placing quadrats, with data collected from 27 plots categorized by size. AGB was estimated via an allometric equation, and aboveground carbon (AGC) was derived from the AGB values. A total of 358 individual trees from 25 species, 24 genera, and 13 families were documented. Species contributing more than 2% to the total AGC were identified as major carbon stock contributors, with Samanea saman demonstrating the highest carbon stock, followed by Pterocarpus indicus f. indicus and Acacia auriculiformis, despite Hibiscus tiliaceus being the most abundant. Spearman’s correlation was also used to find significant correlations between stem length, canopy area, and AGC, with a weak positive relationship between stem length and AGC (rs = 0.166) and a strong positive relationship between canopy area and AGC (rs = 0.631).